Genome-Wide Identification of Circular RNAs Revealed the Dominant Intergenic Region Circularization Model in Apostichopus japonicus - Zhao, Xuelin; Duan, Xuemei; Fu, Jianping; Shao, Yina; Zhang, Weiwei; Guo, Ming; Li, Chenghua (Frontiers in Genetics, 2019)
Circular RNAs (circRNAs) were recently recognized to act as competing endogenous RNAs and play roles in gene expression regulation. Previous studies in humans and silkworms have shown that circRNAs take part in immune regulation. Here, we conducted coelomocyte circRNA sequencing to explore its immune functions in healthy and skin ulceration syndrome (SUS)-diseased sea cucumbers. A total of 3,592 circRNAs were identified in libraries with diversified circularization patterns compared with animal models. The common intron-pairing-driven circularization models are not popular in sea cucumber genome, which was replaced with intergenic region circularization. The accuracy of these identified circRNAs was further validated by Sanger sequencing and RNase R-treated assays. Expression profile analysis indicated that 117 circRNAs were upregulated and 144 circRNAs were downregulated in SUS-diseased condition, of which 71.6% were intergenic-type circRNAs. The interaction network of differentially expressed circRNAs and microRNAs (miRNAs) was constructed and showed that miR-2008 and miR-31, detected with significantly differential expression in SUS-affected samples in a previous study, were predicted to be regulated by 10 and 11 differentially expressed circRNAs with more than 10 binding sites, respectively. Moreover, seven circRNAs were further validated by quantitative real-time PCR, whose variation trends were consistent with circRNA sequencing. All our results supported that intergenic-type circRNAs might have a dominant function in Apostichopus japonicas immune response by acting as miRNA regulators.